2018
DOI: 10.1128/jvi.02190-17
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Modification of Hepatitis B Virus (HBV) Genomes by an Endogenous Cytidine Deaminase inside HBV Cores Informs a Model of Reverse Transcription

Abstract: Cytidine deaminases inhibit replication of a broad range of DNA viruses by deaminating cytidines on single-stranded DNA (ssDNA) to generate uracil. While several lines of evidence have revealed hepatitis B virus (HBV) genome editing by deamination, it is still unclear which nucleic acid intermediate of HBV is modified. Hepatitis B virus has a relaxed circular double-stranded DNA (rcDNA) genome that is reverse transcribed within virus cores from a RNA template. The HBV genome also persists as covalently closed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 73 publications
3
44
0
1
Order By: Relevance
“…However, in its immediately adjacent 1000 to 2000 nts region, the r apo value was the lowest (III area r apo = 1.19; IV area r apo = 1.09), and the subsequent r apo values showed a gradual increase (V region r apo = 1.46; VI region r apo = 2.12). The phenomenon of higher APOBEC‐induced mutation distribution in the minus strand of HBV DNA 1 to 1000 nts region was consistent with the results of previous studies . Nair et al suggested that high APOBEC‐induced mutations in this region might occur during rcDNA synthesis in the viral capsid.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, in its immediately adjacent 1000 to 2000 nts region, the r apo value was the lowest (III area r apo = 1.19; IV area r apo = 1.09), and the subsequent r apo values showed a gradual increase (V region r apo = 1.46; VI region r apo = 2.12). The phenomenon of higher APOBEC‐induced mutation distribution in the minus strand of HBV DNA 1 to 1000 nts region was consistent with the results of previous studies . Nair et al suggested that high APOBEC‐induced mutations in this region might occur during rcDNA synthesis in the viral capsid.…”
Section: Discussionsupporting
confidence: 88%
“…APOBEC‐induced mutations have been found in the HBV DNA sequence and were mainly found in the HBV DNA minus strand . However, these findings mainly emanated from the cell model overexpressing APOBECs and a number of cases of serum and liver cirrhosis tissue samples .…”
Section: Introductionmentioning
confidence: 99%
“…It was firstly reported in 2005 that human APOBEC3 enzymes are able to extensively edit HBV DNA strands via cytidine deamination (77). In HBV-harboring HepAD38 and HepG2.2.15 cells, cytidine deaminases found endogenously could edit 10-25% of the HBV rcDNA genome within the viral capsid (78). Meanwhile, Hsp90 enhances APOBEC-3-mediated DNA deamination activity in HBV (79).…”
Section: Apobec-mediated Deaminationmentioning
confidence: 99%
“…This discrepancy could be explained by the sensitivity of the different G‐A detection methods used. Indeed, the asymmetric deamination pattern of the HBV genome suggested that it was edited by cytidine deaminases during reverse transcription, inside viral nucleocapsids . In this study, cells were not subjected to cytokine treatment to activate APOBEC proteins, and even in these conditions, deamination by endogenously active APOBEC was evident.…”
Section: Indirect Strategies To Affect the Pool Of Closed Circular Dnamentioning
confidence: 66%
“…Indeed, the asymmetric deamination pattern of the HBV genome suggested that it was edited by cytidine deaminases during reverse transcription, inside viral nucleocapsids. 35 In this study, cells were not subjected to cytokine treatment to activate APOBEC proteins, and even in these conditions, deamination by endogenously active APOBEC was evident. Since APOBEC proteins could also inhibit HBV devoid of its deaminase activity, it was hypothesized that this was due to inhibition of minus strand synthesis or pgRNA packaging.…”
Section: Apobec Deamination/degradationmentioning
confidence: 70%